2008
DOI: 10.1016/j.rse.2006.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of woody elements of a Norway spruce canopy on nadir reflectance simulated by the DART model at very high spatial resolution

Abstract: A detailed sensitivity analysis investigating the effect of woody elements introduced into the Discrete Anisotropic Radiative Transfer (DART) model on the nadir bidirectional reflectance factor (BRF) for a simulated Norway spruce canopy was performed at a very high spatial resolution (modelling resolution 0.2 m, output pixel size 0.4 m). We used such a high resolution to be able to parameterize DART in an appropriate way and subsequently to gain detailed understanding of the influence of woody elements contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(68 citation statements)
references
References 67 publications
11
51
0
Order By: Relevance
“…However, that feature implies an increasing number of input variables and computational cost. The difficulty found when inverting more advanced RTMs has been repeatedly acknowledged [23,24]. One of the main drawbacks of advanced RTMs is their long processing time, which impedes the generation of LUTs and inversion strategies and their use in operational processing chains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, that feature implies an increasing number of input variables and computational cost. The difficulty found when inverting more advanced RTMs has been repeatedly acknowledged [23,24]. One of the main drawbacks of advanced RTMs is their long processing time, which impedes the generation of LUTs and inversion strategies and their use in operational processing chains.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental studies, though, demonstrated that these advanced RTMs can be applied in inversion schemes [22][23][24]. However, none of them made it through operational processing chains.…”
Section: Introductionmentioning
confidence: 99%
“…DART forward simulations of vegetation reflectance were successfully verified by real measurements [32] and also cross-compared against a number of independently designed 3D reflectance models (e.g., FLIGHT [26], Sprint [33], Raytran [27]) in the context of the RAdiation transfer Model Intercomparison (RAMI) experiment [34][35][36][37][38]. To date, DART has been successfully employed in various scientific applications, including development of inversion techniques for airborne and satellite reflectance images [39,40], design of satellite sensors (e.g., NASA DESDynl, CNES Pleiades, CNES LIDAR mission project [41]), impact studies of canopy structure on satellite image texture [42] and reflectance [32], modeling of 3D distribution of photosynthesis and primary production rates in vegetation canopies [43], investigation of influence of Norway spruce forest structure and woody elements on canopy reflectance [44], design of a new chlorophyll estimating vegetation index for a conifer forest canopy [45], and studies of tropical forest texture [46][47][48], among others. DART creates and manages 3D landscapes independently from the RT modeling (e.g., visible and thermal infrared IS, LIDAR, radiative budget).…”
Section: Dart Theoretical Background and Functionsmentioning
confidence: 99%
“…The model has been widely applied to broadleaf vegetation to estimate chlorophyll content (Zhang et al 2008, Ma et al 2012, Rivera et al 2013. It has also been successfully recalibrated and used to simulate the optical properties of coniferous needles (Malenovský et al 2008, Morsdorf et al 2009). The model was revised by Feret et al (2008) to improve its performance and applicability.…”
Section: Prospect Model Simulationmentioning
confidence: 99%